The Concept of Fiqh al-Bī’ah in the Qur’an: A Study of the Quranic Verses on Environment in the Ulamas’ Views of Lombok - Subhan Abdullah Acim; Suharti Suharti (Universitas Islam Negeri Mataram, 2023)
This article examines the Qur'anic verses about the environment and the Islamic legal understanding of it (fiqh al-bī’ah) in the view of the ulama of Lombok. This study was based on library resources, compiling the works of Quranic exegesis (tafsīr) and relevant literature, and fieldwork data from the interviews with ulama in Lombok. This study found that the verses of the Qur’an associated with fiqh al-bī’ah can be classified based on the following themes: 1) environmental elements; 2) the diverse ecosystems; 3) the description of ideal and non-ideal environments; 4) the creation of the universe; 5) the purposes of nature’s creation; 6) the causes of natural damage; and 7) the role of humans as caliphs. Second, the interpretation of ulama of Lombok regarding verses related to fiqh al-bī’ah can be classified into seven themes: 1) the procedure for interacting with the environment; 2) the impact of environmental damage; 3) environmental stability as a blessing and grace from Allah; 4) fourth, human immorality as the source of environmental damage; 5) environmental equilibrium and prohibition of environmental damage; 6) the responsibility of leaders in environmental protection; and 7) the urgency of fiqh al-bī’ah.